Voting for Inefficiency - Maria Nieswand; Pio Baake; Lilo Wagner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we propose a probabilistic voter model that rationalizes the ineff cient use of labor input in municipality-owned enterprises. Our focus is on the relationship between absolute as well as relative ineff ciency measures and the size of the municipality in which public rms operate. We show that larger communities maintain enterprises, which are on average more eff cient in absolute as well as relative terms and that e ffciency shows a lower variance for large enterprises. Using data from a sample of electricity distribution companies in Germany we find our theoretical predictions consistent with the companies' observed behavior.
Keywords: H83; L32; D24; 330